Salvage of thumb in a crush injury by a groin flap - Salunke, Prachi P.; Davhale, Pushkar L.; Khedkar, Nayan R.; Kulkarni, Ananta A. (International Surgery Journal, 2023)
The primary function of the hand and fingers is to grasp or manipulate objects of any size or shape with fine touch, strength and the required amount of pressure. The thumb plays a crucial role as unlike other fingers it can work opposite of all digits and carry functions like pinching and grasping, which most of the human activities are dependent on. Crush Injuries of the hand can be severe which can lead to amputation of the digits. Hereby discussing a case of 54-year-old gentleman who met with a road traffic accident with resultant crush injury to the right hand and thumb managed by microsurgery using a groin flap reconstruction of the thumb followed by skeletal stabilization of right-hand digits. The following case report is a concise approach to manage a crush injury with restoration of maximal function of the thumb using a groin flap.